2017
DOI: 10.1098/rstb.2016.0160
|View full text |Cite
|
Sign up to set email alerts
|

Tumour necrosis factor-mediated homeostatic synaptic plasticity in behavioural models: testing a role in maternal immune activation

Abstract: The proinflammatory cytokine tumour necrosis factor-alpha (TNFa) has long been characterized for its role in the innate immune system, but more recently has been found to have a distinct role in the nervous system that does not overlap with other proinflammatory cytokines. Through regulation of neuronal glutamate and GABA receptor trafficking, TNF mediates a homeostatic form of synaptic plasticity, but plays no direct role in Hebbian forms of plasticity. As yet, there is no evidence to suggest that this adapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 104 publications
0
13
0
Order By: Relevance
“…Indeed, numerous MIA models that have used uncharacterized or LMW-PolyIC have yielded offspring with changes in brain and behavioral development (for reviews, (Meyer, 2014; Boksa, 2010; Meyer et al, 2009; Piontkewitz et al, 2012)). At present, it is not clear which maternal cytokines or what magnitude of cytokine change is causally associated with the cascade of altered brain and behavioral development described in previous MIA models (Konefal and Stellwagen, 2017). For example, a recent study found that vitamin D treatment during pregnancy eliminates behavior impairments in MIA-exposed mouse offspring, but surprisingly does not alter pro-inflammatory cytokine levels in dams or in fetal brains (Vuillermot et al, 2017).…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, numerous MIA models that have used uncharacterized or LMW-PolyIC have yielded offspring with changes in brain and behavioral development (for reviews, (Meyer, 2014; Boksa, 2010; Meyer et al, 2009; Piontkewitz et al, 2012)). At present, it is not clear which maternal cytokines or what magnitude of cytokine change is causally associated with the cascade of altered brain and behavioral development described in previous MIA models (Konefal and Stellwagen, 2017). For example, a recent study found that vitamin D treatment during pregnancy eliminates behavior impairments in MIA-exposed mouse offspring, but surprisingly does not alter pro-inflammatory cytokine levels in dams or in fetal brains (Vuillermot et al, 2017).…”
Section: Discussionmentioning
confidence: 91%
“…The TNF-α signaling pathway is mediated by two membrane receptors TNFR1 (also called p55) and TNFR2 (also called p75). TNFR1, which is widely expressed, can be activated by binding to soluble TNF (solTNF) or transmembrane TNF (tmTNF) mediating downstream signaling pathways to initiate apoptosis (86). Compared with TNFR1, TNFR2 expression is limited and mainly released by microglia and endothelial cells known to regulate cell proliferation (87).…”
Section: Tnf-αmentioning
confidence: 99%
“…Previous studies show that high cholesterol diet can increase TNF-α expression in mice [48, 49] and rats [62], our data revealed dietary cholesterol concentrations increased TNF-α expression in the rabbit hippocampus, suggesting dietary cholesterol can model a persistent TNF-α elevation in hippocampus. Since the TNF-α protein we detected by ELISA is a transmembrane protein whose biological functions mainly derive from activation of TNF-α receptor II that is limited to neurons, microglia, and astrocytes [63], this increased endogenous transmembrane TNF-α may cause an imbalance between neuronal protection and neurotoxicity or neuronal damage initiated by TNF-α receptor I and II [64], and eventually lead to loss of homeostasis in vulnerable sites such as synapses that are responsible for learning and memory [65]. Most importantly, hippocampal neuroinflammation in cholesterol-fed rabbits occurred in the absence of neurodegenerative changes and was independent of amyloid accumulation in both cerebral cortex and hippocampus [66], and thus cholesterol diet-associated endogenous TNF-α elevation and neuroinflammation in hippocampus may be involved in learning and memory changes observed in this rabbit model of AD [1, 41, 45, 67].…”
Section: Discussionmentioning
confidence: 99%